ANALISA KEPUTUSAN PEMBELIAN PAKAIAN BEKAS (STUDI PADA MAHASISWA FEB UPN VETERAN JAKARTA) - Elsa Kirana Fauziah (2022)
Reduced income due to the pandemic has made one of the businesses, namely the thrift business, an alternative for new income for used clothing traders in the midst of a pandemic and has grown to date. Used clothing is a growing trend in today's fashion needs. Currently there are several phenomena that influence purchasing decisions so the purpose of this study is to determine the influence of social media, lifestyle and price on purchasing decisions. The target population in this study were active students of the Faculty of Economics and Business at UPN Veterans Jakarta, with a sample of 100 respondents using a non-probability sampling technique with a purposive sampling method. This research uses quantitative methods. The test tool used is Smart PLS 3.0. The results of this study indicate (1) there is a significant influence of social media on purchasing decisions, (2) there is a significant influence of lifestyle on purchasing decisions, (3) there is a significant influence of price on purchasing decisions